Competence, workload, and motivation as predictors of employee performance : Case Study in DPRD Muara Enim Regency - Harmison Harmison; Marzuki Alie (Institute of Computer Science (IOCS), 2026)
This study aims to analyze and examine the partial and simultaneous effects of competence, workload, and motivation on the performance of employees at the Secretariat of the Regional House of Representatives (DPRD) of Muara Enim Regency. The research employs a quantitative method with a survey, confirmatory, and verificative approach. This study is classified as associative research focusing on the relationships among variables. The research population consists of 90 employees, all of whom were included as the research sample using a saturated sampling technique. The data comprise primary and secondary data, collected through observation, questionnaire-based interviews, and documentation. Data analysis was conducted using multiple linear regression using SPSS version 30. The results indicate that competence and motivation have a significant positive effect on employee performance, while workload has a significant negative effect on employee performance. Simultaneously, employee performance is positively and significantly influenced by the combination of competence, workload, and motivation. These three variables demonstrate a substantial relationship in improving employee performance. This research contributes to developing comprehensive human resource management science and further research in this field. Improving employee performance can be done by simultaneously paying attention to aspects of competence, workload, and motivation